2020
DOI: 10.1002/cssc.201903222
|View full text |Cite
|
Sign up to set email alerts
|

Porosity‐Engineering of MXene as a Support Material for a Highly Efficient Electrocatalyst toward Overall Water Splitting

Abstract: The use of 2 D transition metal carbide MXenes as support materials to incorporate catalytically active compounds is of interest because of their unique properties. However, the preparation of well‐dispersed catalytic phases on the inter‐connected porous MXene network is challenging and has been rarely explored. This work focuses on the synthesis of basal‐plane‐porous titanium carbide MXene (ac‐Ti3C2) that is used subsequently as an effective host for the incorporation of a known catalytically active phase (Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…MXenes are metal carbide or nitride materials with a two‐dimensional (2D) structure, which attracted a large interest recently for a broad range of applications such as materials for energy and environmental applications, [1–4] and catalysis [5–7] . In the latter area, several papers deal on N 2 fixation (NRR), [8–18] a topic of current large interest to directly produce ammonia from nitrogen [19] .…”
Section: Figurementioning
confidence: 99%
“…MXenes are metal carbide or nitride materials with a two‐dimensional (2D) structure, which attracted a large interest recently for a broad range of applications such as materials for energy and environmental applications, [1–4] and catalysis [5–7] . In the latter area, several papers deal on N 2 fixation (NRR), [8–18] a topic of current large interest to directly produce ammonia from nitrogen [19] .…”
Section: Figurementioning
confidence: 99%
“…[ 88 ] PGMs supported on MXenes have been studied for OER, with PtO a PdO b /Ti 3 C 2 T x and IrCo/Ti 3 C 2 T x showing promising OER performance. [ 89,90 ] Non‐precious metals supported on MXenes for OER also draw great attention, especially for Co‐, Ni‐, and Fe‐based catalysts. For instance, strong interfacial interactions between Co 3 O 4 and Ti 3 C 2 T x contribute to improved OER activity and stability.…”
Section: Applications In Electrocatalysismentioning
confidence: 99%
“…demonstrated that the engineering of porous and conductive support effects of 2D transition‐metal carbide MXenes through a wet chemical route could greatly enhance the overall water splitting performance. The improvement can be attributed to the synergistic effect of the porous surface of supporting material with the generated abundant of macro/meso/micropores can only afford high density of well‐distributed active sites but also can efficiently shorten the ion/mass transport migration pathways and increase the electrolyte accessibility in the catalysis …”
Section: Strategies To Enhance Overall Water Splitting Catalyzed By Tmentioning
confidence: 99%